Efektivitas Sikat Gigi Listrik sebagai Kontrol Plak Penderita Sindrom Down - Budirahardjo, Roedy; Tarmizi, Thariq Ibnu; Fatmawati, Dwi Warna Aju; Suci Dharmayanti, Agustin Wulan (Jurnal Kesehatan, 2023)
Down Syndrome is a genetic disorder on chromosome 21 that interferes with growth, development, and physical activity, including brushing teeth. Electric toothbrushes are expected to optimize plaque control because they do not require special techniques. This study was an observational analytic using a Within-subject design. This study was carried out at three inclusive schools in Jember district from September to October 2019, which the subjects of studies were 30 students. Plaque index assessment used the Loe and Silness method by examining 6 teeth and 4 surfaces. The subjects were examined before and after brushing their teeth using a manual toothbrush, and after one week, they used an electric toothbrush. The procedure for using an electric toothbrush is the same as in a manual toothbrush. The data were difference analyzed. The sign test analysis obtained significant results in the plaque index score before and after brushing teeth using a manual toothbrush and an electric toothbrush (p<0.05). There was also a significant difference in the plaque index score in using manual and electric toothbrushes (p<0.05). Briefly, an electric toothbrush was an effective plaque control for Down syndrome.